2005
DOI: 10.1007/s11207-005-4999-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Solar Radius in Antalya between 2001–2003

Abstract: The results of the solar radius measurements from February 2001 to November 2003 with the solar astrolabe at the TUBITAK National Observatory are presented. The mean semi-diameter for the period, corrected for systematic effects such as the Fried parameter and the zenith distance, is found to be 959.29 ± 0.01 arc sec. A comparison of the monthly averages of the solar radius with the monthly means of sunspot numbers shows that the semi-diameter of the Sun increases with an amplitude of 0.017 arc sec per year in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Specific details of these results have been presented by Delmas et al (2003b), Kiliç et al (2003) and Penna et al (2003). It is worth mentioning here that the sufficiently long standing use of the method and algorithms, both at the same and at different stations, ensures that the features here examined and previously not present cannot be ascribed to defects of the program routines.…”
Section: Introductionmentioning
confidence: 84%
“…Specific details of these results have been presented by Delmas et al (2003b), Kiliç et al (2003) and Penna et al (2003). It is worth mentioning here that the sufficiently long standing use of the method and algorithms, both at the same and at different stations, ensures that the features here examined and previously not present cannot be ascribed to defects of the program routines.…”
Section: Introductionmentioning
confidence: 84%
“…The time series corresponding to a set of more than 3700 independent and homogeneous values was recorded with a CCD video camera at the three zenit distances under different atmospheric conditions. The previous studies indicated that a linear decrease of the observed solar diameter with the atmospheric turbulence effect is present (Irbah et al 1994;Sinceac 1998;Sinceac et al 1998;Chollet & Sinceac 1999; Kiliç, Golbasi & Chollet 2005). To correct this effect causing important errors on solar radius measurements, and to obtain more homogeneous values for the solar radius, we have used a method improved by Sinceac (1998) and (Chollet & Sinceac 1999).…”
Section: Observationsmentioning
confidence: 99%
“…Thus, the data of each year are corrected independently for this effect by reducing all diameter measurements to 1/r 0 (Kiliç, Golbasi & Chollet 2005). The yearly mean values of the CSD obtained in this way and other parameters are given in Table 1.…”
Section: Observationsmentioning
confidence: 99%
“…One of these widely used instruments is the solar astrolabe. The description of the visual and CCD generation of this instrument and the results obtained for the diameter of the Sun are given by Laclare et al (1991Laclare et al ( , 1996Laclare et al ( , 1999, Delmas et al (2006), Andrei et al (2004), Gölbaşi et al (2000Gölbaşi et al ( , 2001, Jilinski et al (1999), Penna et al (2002), and Kilic et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…To show this, we compare three filtering methods using the CCD solar astrolabe data, i.e., the proposed method (see Djafer et al 2008b) based on the compact wavelet that automatically determines the amplitude of the noise present in the image and eliminate it without changing the inflection point position, the FFTD method (see Sofia et al 1983Sofia et al , 1994Egidi et al 2006), and the method actually used with the CCD solar astrolabe (see Sinceac et al 1998;Jilinski et al 1999;Kilic et al 2005). …”
Section: Introductionmentioning
confidence: 99%